Penerimaan Khalayak Non Perokok Usia 16-21 Tahun di Kota Denpasar Terhadap Tayangan Iklan Rokok Gudang Garam di Televisi - Aditi, Made Gayatri Dharma; Pradipta, Ade Devia; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium, 2024)
In Indonesia, cigarette TV commercial are still allowed to showed on television but can not show products, and smoking scenes. For example, Gudang Garam TV commercial, which always makes advertisements with persuasive. By using Stuart Hall's reception theory, this study aims to determine the acceptance of non-smokers aged 16-21 years in Denpasar City in understanding TV commercial for Gudang Garam cigarettes. This research uses qualitative research methods with a post-positivism paradigm. The results of this study indicate that the majority of informants 3 out of 6 informants, accept and understand the concepts and meanings of the Gudang Garam TV commercial, but the advertisement has not succeeded in making them want to buy the product and change from non-smokers to be smokers so that they enter the Negotiated Position. Then there are 2 people with Oppositional Position and 1 informant with Dominant Position. Keywords : Persuasive, Cigarette Advertising, Television, Stuart Hall Reception Analysis